A COMPARATIVE SEMANTIC AND LINGUOCULTURAL ANALYSIS OF THE CONCEPT “WOMAN” IN UZBEK AND ENGLISH (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article presents a comparative semantic and linguocultural analysis of lexical units representing the concept “woman” in Uzbek and English. The study examines denotative and connotative meanings, socio-cultural motivations, and gender-related semantic shifts reflected in both languages. The findings demonstrate that in Uzbek linguistic consciousness the concept is strongly associated with family roles, moral responsibility, modesty, and honour, whereas in English it reflects individuality, equality, autonomy, and social independence. The research confirms that semantic differences are rooted not only in lexical structures but also in cultural schematization and cognitive framing. The study contributes to gender linguistics, cross-cultural semantics, and linguoculturology.